Development of decision support system using OLAP-technologies for information security monitoring systems - Dashdamirova, K.Q. (Проблеми програмування, 2022)
The article highlighted the need for continuous monitoring of the computer networks (CN) for information security and analyzed the sources of data for information security monitoring (ISM). Methods of data collection from various sources have been investigated, and categories of ISM systems have been studied. The architectural-technological model of the system supporting decision-making based on OLAP (Online Analytical Processing) and data warehouse has been proposed for quick response to security-related incidents and detected incidents in ISM systems. У статті висвітлено необхідність постійного моніторингу комп’ютерних мереж з метою забезпечення інформаційної безпеки та проаналізовано джерела даних для моніторингу інформаційної безпеки. Досліджено методи збору даних з різних джерел, досліджено категорії систем моніторингу інформаційної безпеки. Запропоновано архітектурно-технологічну модель системи підтримки прийняття рішень на основі OLAP (Online Analytical Processing) і сховища даних для швидкого реагування на інциденти безпеки та виявлені інциденти в системах моніторингу інформаційної безпеки.